(untitled) (Research, Society and Development, 2021)
The incentives offered to boys and girls are different, based on socio-cultural differences instituted over the centuries. Objective: To analyze the language development of children in a public daycare center and to verify possible associations of the linguistic outcome with difference between genders. Method: This is a cross-sectional study, carried out on 62 children, aged 3 to 6 years. The instrument used was the Denver II Development Screening Test. To compare the mean scores, the Mann Whitney nonparametric test was used, with a significance level of 5% (p <0.05). Results: The association of the Denver II outcome with gender showed that the girls obtained higher average scores, highlighting: it comprises 3 adjectives (0.94 ± 0.25), recognizes 4 actions (0.94 ± 0.25) and defines 3 objects for use (0.97 ± 0.18). Conclusion: Female children have a more favorable outcome in the speech acquisition process compared to men.